VIVVOTE / Shahidah Abd Razak ... [et al.] - Abd Razak, Shahidah; Lokman, Asmidar; Hamid @ Hussain, Shawal Sahid; Ahmad, Nur Khairunnisa Liyana (2021)
Voting is an act of civic participation in a community. It is the engagement between people in the community and the structure of the government. Civic participation in a community is being influenced by several factors such as knowledge, decision-making skill, attitude, and values. Since the awareness of voting among young people is still low, many of them are eligible voters but not registered due to their indifference towards voting responsibly. Many are reported as not interested to vote. As Malaysia has legislated the new law of 18 years as the minimum age to vote thus in 2023, all 18 years old will perform their civic duties as a citizen of this country to vote in the 15th General Election. Their participation and decision-making in the community are crucial. The purpose of this product is to create awareness among new young voters in executing their civic responsibility in the community. It is also offering an insight to the policymakers in strategizing the approach to encourage young people to go out and vote. Based on the model of forming a civic competence, this product/framework aims to assist the government in cultivating the value of civic participation among young people through voting. A survey was conducted to identify the level of civic participation and voting awareness among young people in the country. The survey found that the majority of the respondents are aware of voting responsibility and actively participate in their community.